Colonização, progresso e movimento de emancipação : Norte de Mato Grosso uma discussão pós-70 - Giachini, Ivonete (2011)
From 1970 on the state of Mato Grosso suffers significant changes, resulting in the dismemberment of the South region in 1977 that resulted in Mato Grosso do Sul and the promotion of federal politics of occupation of Amazoniam, which resulted in the expansion of the border agricultural in the Northern of the State. The intense migration mainly of the south of the country for the areas of colonization, promoted for the government and, in partnership with private companies, contributed to occur in a few years in Northern of Mato Grosso, the accelerated development of process of urbanization and of agricultural business. Since 1980 are publicized in newspapers, especially in the newspapers of regional circulation, articles that portray the north of Mato Grosso as a space of progress . These publications emphasize that, despite the short time since the arrival of these migrants, the region developed differently from the rest of the state. The differentiation, mainly cultural, added at the territorial extension, at distance of the capital, the lack of infrastructure, result of little performance of the state government in the Northern of the state and the legacy of the southern colonization are some of the reasons (arguments) used for supporters of the separatist cause. The dissatisfaction took at the organized of the secessionist movement, which in the years 1995, 1999, 2000, 2001 and 2003 succeeded through of congressmen, that were drawn Projects Legislative Decrees (PDLs), aiming at the popular consultation for the emancipation of these region with the creation of one or more federal units.